Enhancing Knowledge Accessibility and Preservation - Mohammad Anthony Gufron; Kun R. Wardhana; Dana I. Sensuse; Jonathan S. Lusa; Nadya Safitri (Eduvest - Journal of Universal Studies, 2026)
In the era of digital transformation, effective knowledge management has become essential for organizations to maintain operational continuity, improve productivity, and preserve critical institutional knowledge. The IT Department of Bank ABC faces challenges related to fragmented knowledge storage, limited accessibility to technical information, and potential knowledge loss due to employee turnover. These conditions affect the efficiency of knowledge-sharing processes and employees’ ability to retrieve relevant information when needed. This research aims to design a knowledge repository system that enhances knowledge accessibility and supports the preservation of organizational knowledge within the IT Department of Bank ABC. This study employed a qualitative approach through stakeholder interviews and literature reviews to identify knowledge management challenges, define knowledge requirements, and develop a repository design framework. The analysis was conducted using the SECI knowledge management model, knowledge taxonomy, and User-Centered Design (UCD) approach, supported by Unified Modeling Language (UML) modeling. The results indicate that the proposed repository design can organize operational and technical knowledge into structured domains while providing essential features, including document management, knowledge categorization, search functionality, role-based access control, approval workflows, and audit trails. The proposed system design contributes to improving knowledge accessibility, reducing knowledge silos, and strengthening organizational memory. In conclusion, the knowledge repository provides a strategic framework for Bank ABC’s IT Department to manage, preserve, and utilize knowledge effectively. Future implementation and usability evaluations are recommended to measure its practical impact.